A Technological Monitoring Architecture for Academics' Mental and Physical Health - Leão, Wagno Sérgio; Silva, Gabriel Di iorio; Ströele, Victor; Dantas, Mário; Campos, Fernanda; Braga, Regina; David, José Maria N. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2022)
Educational institutions are moving to a hybrid model that allows onsite and online classes. Students and teachers must adapt to these changes in the teaching and learning routine, leading them to stress and anxiety moments. This work proposes an architecture to assist academics in detecting these stressful moments during daily activities. The proposal uses smart bands, machine learning algorithms, and a smartphone app for environment monitoring. The evaluation was conducted by collecting real data from heart rate spikes and enriching it using the location information to send recommendations. The results show that it is possible to identify stressful moments by respecting the academics environment by monitoring their routine.